2007
DOI: 10.1124/jpet.106.118927
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Characterization of Sch527123, a Potent Allosteric CXCR1/CXCR2 Antagonist

Abstract: In neutrophils, growth-related protein-␣ (CXCL1) and interleukin-8 (CXCL8), are potent chemoattractants (Cytokine 14:27-36, 2001; Biochemistry 42: 2874 -2886, 2003) and can stimulate myeloperoxidase release via activation of the G protein-coupled receptors CXCR1 and CXCR2. The role of CXCR1 and CXCR2 in the pathogenesis of inflammatory responses has encouraged the development of small molecule antagonists for these receptors. The data presented herein describe the phar-, a novel antagonist of both CXCR1 and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
97
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(104 citation statements)
references
References 33 publications
7
97
0
Order By: Relevance
“…2). The obtained pK i values of both the diarylurea and pyrimidine compounds are in good agreement with earlier published data (White et al, 1998;Podolin et al, 2002;Catusse et al, 2003;Ho et al, 2006;Gonsiorek et al, 2007). All tested compounds were able to inhibit CXCL8-induced ␤-arrestin2 recruitment in human CXCR2-transfected cells, with a rank order of SB332235 ϳ SB265610 Ͼ SB225002 ϳ VUF10948 Ͼ compound 1 Ͼ compound 3 Ͼ compound 2 (Fig.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…2). The obtained pK i values of both the diarylurea and pyrimidine compounds are in good agreement with earlier published data (White et al, 1998;Podolin et al, 2002;Catusse et al, 2003;Ho et al, 2006;Gonsiorek et al, 2007). All tested compounds were able to inhibit CXCL8-induced ␤-arrestin2 recruitment in human CXCR2-transfected cells, with a rank order of SB332235 ϳ SB265610 Ͼ SB225002 ϳ VUF10948 Ͼ compound 1 Ͼ compound 3 Ͼ compound 2 (Fig.…”
Section: Discussionsupporting
confidence: 79%
“…Hence, all the CXCR2 antagonists of the different chemical classes tested in this study displace and antagonize CXCL8, most probably via a noncompetitive, allosteric mechanism. This mechanism of action is common for other small antagonists targeting chemokine receptors (Gonsiorek et al, 2007;Verzijl et al, 2008). The allosteric inhibition by the tested CXCR2 antagonists is expected, as in general chemokines, like CXCL8, are thought to bind to the extracellular part of the GPCR protein (Rajagopalan and Rajarathnam, 2006;Allen et al, 2007;Viola and Luster, 2008), notably the N terminus and the extracellular loops.…”
Section: Discussionmentioning
confidence: 96%
“…In fact, recombinant CXCL8 was shown to protect B-CLL cells from cytotoxic effects caused by the cytostatic drugs chlorambucil and fludarabin [39]. Several approaches to inhibit CXCR1 and CXCR2 have been undertaken, mostly in the context of inflammation in airway diseases, with proven efficacy in several animal models and ongoing phase II clinical trials for chronic obstructive pulmonary disease [41][42][43][44][45]. To date, there is no report on CXCR1/CXCR2 inhibition in B-CLL.…”
Section: Cxcl8 (Il-8) and Its Receptors Cxcr1 And Cxcr2mentioning
confidence: 99%
“…SCH-527123, as a novel and selective antagonist of the CXCR2, has shown efficacy in the treatment of inflammatory diseases (17). Moreover, Singh and colleagues showed that SCH-527123 treatment inhibited human melanoma cancer growth and colorectal cancer liver metastases by decreasing tumor cell proliferation, angiogenesis, and enhancing the apoptosis of malignant cells (18,19).…”
Section: Introductionmentioning
confidence: 99%